2020
DOI: 10.1016/j.jns.2020.117006
|View full text |Cite
|
Sign up to set email alerts
|

Neurological impact of emboli during adult cardiac surgery

Abstract: This study draws on advances in Doppler ultrasound bubble sizing to investigate whether high volumes of macro-bubbles entering the brain during cardiac surgery increase the risk of new cerebral microbleeds (CMBs), ischemic MR lesions, or post-operative cognitive decline (POCD). Methods: Transcranial Doppler (TCD) ultrasound recordings were analysed to estimate numbers of emboli and macrobubbles (>100 μm) entering the brain during cardiac surgery. Logistic regression was used to explore the hypothesis that embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…Even more air bubbles were found in patients undergoing open-heart surgery. Similar findings were obtained in their following study [ 8 ]. Interestingly, bubbles in the brain due to the administration of drugs or blood draws were reported only once.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Even more air bubbles were found in patients undergoing open-heart surgery. Similar findings were obtained in their following study [ 8 ]. Interestingly, bubbles in the brain due to the administration of drugs or blood draws were reported only once.…”
Section: Discussionsupporting
confidence: 92%
“…The almost spontaneous and logical association with neurological complications occurring after open-heart surgery, which range from 1 to 6% for stroke [3][4] but up to 76% for silent brain micro-infarcts or micro-bleeds [5][6], could not be established beyond doubt. The same applies to the relationship between air micro-embolism and the described cognitive decline affecting a variable percentage of patients after open-heart surgery [7][8][9][10]. The pathogenesis of adverse neurologic outcome depends on both patient-related risk factors and procedure-related events, so gaseous microemboli may be only one of the contributing factors to a multifactorial problem (Unpublished original research article: Kopjar T, "Silent Brain Injury Associated to Postoperative Cognitive Decline after Coronary Bypass Surgery", 32nd EACTS annual meeting, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…During open-heart surgery, however, the opening of the circulation exposes blood to air, which results in the formation of air bubbles on the blood surface, especially in the left ventricle and the right upper pulmonary vein [ 1 ], which may embolize later with the risk of critical organ damage. Recent studies with pre- and post-operative psychological assessments and improved imaging techniques have found that much more covert brain insults and micro-bleeds are caused by open-heart surgery than originally thought [ 2 ]. Despite this fact, many surgeons routinely use a preventive technique called “field-flooding”, which begs the question, is this technique effective [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently the interest in neurological damage and cognitive dysfunction resulting from air emboli has increased thanks to improved assessment methods and imaging modalities, and the findings are astonishing. Patel and colleagues, for example, combined pre- and post-op MRI and neuropsychological tests with peri-operative quantification of air emboli via transcranial Doppler in cardiac surgery patients and counted thousands of bubbles in each patient [ 4 ]. They discovered new cerebral microbleeds in more than 80% of the patients undergoing valve surgery (significantly more than CABG) and new brain lesions and neuropsychological decline in more than 40% of the patients.…”
Section: Introductionmentioning
confidence: 99%